Crustaceans - Salvatore, Kaitlyn; Propis, Brianna; Flynn, Michael (Buffalo, NY : Britannica Educational Publishing IN ASSOCIATION WITH THE ROSEN PUBLISHING GROUP, 2025)
"Have you ever seen or eaten lobster and shrimp? If so, you're already familiar with crustaceans! Crustaceans have segmented bodies, jointed limbs, and two pairs of antennae. Throughout this volume, readers learn about the different types of crustaceans, including decapods, amphipods, copepods, and others. Readers learn about the similarities and differences of each kind of crustacean, as well as familiarize themselves with less recognizable ones like the wood louse and zooplankton. Full-color photographs accompany achievable text to enhance the readers' experience and help them to understand the information"--
Includes bibliographical references and index
Keywords: Crustacea -- Juvenile literature; Juvenile works; Juvenile literature